Investment process manual and ratio analysis of Export Import Bank of Bangladesh Limited - Islam, Kazi Shahariyar (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.